1977
DOI: 10.1021/bi00624a025
|View full text |Cite
|
Sign up to set email alerts
|

Active proton uptake by chromaffin granules: observation by amine distribution and phosphorus-31 nuclear magnetic resonance techniques

Abstract: The hydrogen ion activity within isolated chromaffin granules can be estimated from the distribution of the weak base methylamine and from phosphorus-31 nuclear magnetic resonance spectra of ATP contained in the granules. Following the addition of ATP to the external medium, the internal pH drops by 0.2 to 0.5 unit. This change occurs only in medium containing a permeant anion such as chloride and is abolished by an uncoupler of oxidative phosphorylation. These results indicate that the chromaffin granule memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(105 citation statements)
references
References 22 publications
6
99
0
Order By: Relevance
“…The experiments shown in Figs. 4 and 5 demonstrate this phosphorylation reaction in the NMR sample tubes. The spectrum of Fig.…”
Section: Phosphorylationmentioning
confidence: 82%
See 1 more Smart Citation
“…The experiments shown in Figs. 4 and 5 demonstrate this phosphorylation reaction in the NMR sample tubes. The spectrum of Fig.…”
Section: Phosphorylationmentioning
confidence: 82%
“…Peak positions of 31P resonances were expressed in parts per million (ppm) from an external reference of 85% HaPO4. Recently high-resolution 31P nuclear magnetic resonance (NMR) technique has been used to study metabolic processes in various cells (1), tissues (2,3), cell organelles (4), and even in perfused animal organs (5,6). -The technique provides considerable information on various phosphate metabolites in tvvo.…”
mentioning
confidence: 99%
“…NMR has a unique advantage over most investigation procedures in that it allows a non-invasive inspection of even the most delicately balanced system. This property has been used to advantage in studying a range of complex, intact systems such as muscle [5], bacteria [6,7] and chromaffin granules [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…ATPase activity (8)(9)(10)(11), ATP-dependent proton translocation (12), and ATP-dependent changes in the fluorescence of 1-anilino naphthalene-8-sulfonate (ANS) (11) have been detected in intact granules or membrane vesicles prepared from chromaffin granules by osmotic shock. Moreover, it has been demonstrated that an uncoupler-sensitive pH gradient (ApH, interior acid) is maintained across the chromaffin granule membrane (13)(14)(15). These findings have led to the proposal that the membrane-bound ATPase in chromaffin granules is a proton-translocating enzyme that generates a proton electrochemical gradient (interior acid and positive) and that the low internal pH may have a dual role in the mechanism of catecholamine uptake and storage: (i) it may provide the driving force for catecholamine accumulation (putatively, the catecholamine is translocated across the membrane in its unprotonated form and accumulation results from protonation in the intragranular space); and (Ui) it may prevent oxidation of intragranular catecholamines.…”
mentioning
confidence: 99%
“…The identification of a membrane-bound ATPase (12), as well as the demonstration of ATP-dependent changes in ANS fluorescence (11) and the existence of a ApH across the granule membrane in the presence of ATP (13)(14)(15), indicate that this ATPase generated a proton electrochemical gradient (internal acid and positive) as a result of ATP hydrolysis. It is likely, therefore, that the electrochemical proton gradient or one of its components-i.e., ApH or the membrane potential (A#1, interior positive)-was the immediate driving force for epinephrine accumulation in chromaffin granules.…”
mentioning
confidence: 99%